(untitled) (Applied Biological Research, 2015)
The present study was aimed to assess clinic-haematological changes in cows showing hoof and horn abnormalities, rearedaround Koradi Thermal Power Plant, Nagpur, Maharashtra (India). Hoof and horn abnormalities are usually attributed to selenium toxicity. Twenty cows were randomly selected within a radius of 5 km of thermal power plant. Blood, urine and milk samples were analyzed for haemato-biochemical changes. Also, the selenium level was estimated and compared with control samples taken from Deolapar Cattle Farm and Agriculture CollegeDairy Farm (located within the same agro-climatic conditions but away from the impact area of fly ash). Mean selenium value in blood of exposed animals was insignificantly higher than unexposed animals while selenium in urine and milk of exposed cows was significantly higher than control though within the permissible range. The haemato-biochemical parameters viz., haemoglobin, AST, ALT, serum creatinine and BUN of exposed cows were insignificantly less than control cows. Air, water, soil and fodder samples, collected from the study area, showed the selenium level of 3 ng m-3, 0.001±0.002 ppm, -0.593 ppm and 1.25±0.20 ppm, respectively. It appears that the selenium level in impact area has not reached to the level that may develop selenium toxicity like sloughing of horns, weakness and hoof deformity; and the symptoms observed are due to the factor other than selenium toxicity.